Memantine for agitation/aggression and psychosis in moderately severe to severe Alzheimer's disease: a pooled analysis of 3 studies. - Wilcock, G; Ballard, C; Cooper, J; Loft, H (2008)
OBJECTIVE: Long-standing evidence indicates that Alzheimer's disease patients with behavioral symptoms have a worse prognosis and a more rapid disease progression. The current retrospective analysis evaluated the efficacy and safety of memantine in a subpopulation of patients with Alzheimer's disease exhibiting behavioral symptoms of agitation/aggression or psychosis at baseline. METHOD: A pooled analysis was conducted in people with agitation/aggression or psychosis from 3 large 6-month, randomized studies in moderately severe to severe Alzheimer's disease. The effect of memantine and placebo on these specific symptoms was evaluated using the Neuropsychiatric Inventory (NPI) subitem cluster of agitation and psychosis. Outcomes on global, cognitive, and functional measures were also analyzed. RESULTS: Sixty percent of the total patient group had baseline symptoms of agitation/aggression, delusions, or hallucinations on the NPI. At both 12 and 24/28 weeks, there was a significant treatment advantage for memantine over placebo for the proportion of patients showing improvement on the defined neuropsychiatric symptom cluster (55.6% vs. 44.4% at week 12, p = .008; 58.0% vs. 44.8% at week 24/28, p = .002) and specifically for the treatment of agitation/aggression (55.3% vs. 43.1% at week 12, p = .011; 61.0% vs. 45.0% at week 24/28, p < .001). Placebo-treated patients in this population demonstrated an accelerated disease progression for global (Clinician's Interview-Based Impression of Change Plus Caregiver Input), cognitive (Severe Impairment Battery), and functional (Alzheimer Disease Cooperative Study Activities of Daily Living Inventory 19-item scale) outcomes, but memantine conferred statistically significant benefit for all measures. Tolerability in this population remained good, and fewer memantine-treated patients than placebo-treated patients withdrew due to adverse events. CONCLUSIONS: This post hoc analysis provides important evidence from placebo-controlled trials that memantine may be a safe and effective treatment in Alzheimer's disease patients with agitation/aggression or psychosis, who are otherwise prone to rapid progression. Memantine treatment provided benefits in cognitive, functional, and global outcomes in these patients and for their agitation/aggression.